The Effect of Providing Family Center Care Education Using Booklets on the Knowledge Level of NICU Nurses in Hospitals - Tungga Dewi; Alfonsa Reni Oktavia; Heny Fitriany; Ety Ernawaty; Vania Octo; Sus Dwi Riantini; Sisilia Sisilia Prima Yanuaria Buka (Medicor : Journal of Health Informatics and Health Policy, 2026)
Family-Centered Care (FCC) is an important approach to care in the Neonatal Intensive Care Unit (NICU) because it actively involves families in infant care. However, the implementation of FCC still requires increased understanding among nursing staff. This study aimed to determine the effect of providing family-centered care education using a booklet on the knowledge level of NICU nurses in a hospital. Preliminary study showed that only 40% of nurses at MHJS hospital understood the concept of Family-Centered Care. The aim was to assess the effectiveness of FCC education using booklet media on the level of knowledge of NICU nurses at MHJS. This study applied a quasi-experimental design with measurements before (pre-test) and after (post-test) the intervention. Eighteen NICU nurses were included using a total sampling technique. The intervention consisted of Family-Centered Care (FCC) education delivered through a booklet. Data were collected in January 2021 using a 15-question questionnaire to assess nurses' knowledge before and after the intervention. Before completing the questionnaire, researchers provided an explanation and obtained informed consent from all respondents. The findings demonstrate that the average pre-test score was 22.6 out of 30, while the post-test score increased to 26.5 out of 30. Statistical analysis showed a significant increase in knowledge after the intervention, with a statistically significant increase in knowledge Asymp. Sig. (2-tailed); p value = 0.000 (Wilcoxon Signed Rank). Using the booklet media in FCC education significantly increased the knowledge of NICU nurses.